2022
DOI: 10.1111/ijpo.12997
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term effects of primary school‐based obesity prevention interventions in children: A systematic review and meta‐analysis

Abstract: Introduction: This systematic review and meta-analysis investigate the long-term effects of primary school-based obesity prevention interventions on body-mass index (and z-scores), waist circumference (and z-scores) and weight status.Methods: Four databases were searched for studies from date of inception until June 8th, 2021. We included randomized controlled trials (RCT) and non-RCTs investigating effects ≥12 months post-intervention of primary school-based interventions with intervention duration ≥6 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Thirty-one SRs were included in this umbrella review . SRs examined nutrition interventions for pediatric obesity prevention in all settings combined [20,22,30,33,34,43,44,47] or in the home and family [20,22,35], healthcare [22,37,49,50], school [20,22,23,25,[27][28][29]36,38,[40][41][42]46], or community settings [21,22], or examined the efficacy of food assistance programs [24,26,27,31,32,39] or electronic interventions [45,48]. The study selection process is described in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty-one SRs were included in this umbrella review . SRs examined nutrition interventions for pediatric obesity prevention in all settings combined [20,22,30,33,34,43,44,47] or in the home and family [20,22,35], healthcare [22,37,49,50], school [20,22,23,25,[27][28][29]36,38,[40][41][42]46], or community settings [21,22], or examined the efficacy of food assistance programs [24,26,27,31,32,39] or electronic interventions [45,48]. The study selection process is described in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen SRs examined the impact of obesity prevention interventions with nutrition in the school setting in all age groups combined [20,23,[27][28][29]38,40], children ≤ 5 years old [22], children 6-12 years old [22,25,36,41,42,46] and adolescents 13-18 years old [22]. No studies reported the cost-effectiveness of these interventions.…”
Section: School Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous interventions to prevent childhood overweight and obesity focused mainly on dietary and/or physical activity interventions in schools (13)(14)(15)(16)(17)(18)(19). The prior interventions generally showed no or only small effects on weight development (13)(14)(15)(16)(17)(18)(19), and the evidence of long-term effects is limited (14,20). It is therefore increasingly argued that preventing childhood overweight and obesity requires multi-component and multi-setting interventions, which focus not only on individual health behaviors, but also on changing the structural environments in which children and their families live (21-23).…”
Section: Prior Interventions To Prevent Childhood Overweight and Obesitymentioning
confidence: 99%